2000
DOI: 10.21273/hortsci.35.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Pollen of Two Fruit Crop Cacti of the Genus Hylocereus Is Affected by Temperature and Duration of Storage

Abstract: Hylocereus undatus (Haw.) and H. polyrhizus (Weber) are new fruit crops of the Cactaceae. In Israel, flowers of the two species, which are self-incompatible, are hand cross-pollinated. In order to ensure a current supply of compatible pollen and guarantee good yields, we have developed a procedure for long-term storage of pollen. Pollen for storage was collected in the evening or in the morning. Its moisture content ranged between 45% to 50% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…The results of in-vitro pollen germination and pollination combinations at various temperature treatments confirmed the previous hypothesis that HT reduces pollen viability, resulting in poor fertilization and small fruit size in "Da Hong" red-fleshed pitaya [6]. Metz et al [33] revealed that the in-vitro germination rate of "clone C" red-fleshed pitaya decreased to <11% when pollen was stored for 3 months, but when the pollen intensity (pollen amount) was sufficient, the pollen remained able to promote fruit set by artificial pollination. Therefore, although pollen viability was significantly reduced under MH treatment, the function of the pistil was less affected by HT treatment.…”
Section: Discussionsupporting
confidence: 82%
“…The results of in-vitro pollen germination and pollination combinations at various temperature treatments confirmed the previous hypothesis that HT reduces pollen viability, resulting in poor fertilization and small fruit size in "Da Hong" red-fleshed pitaya [6]. Metz et al [33] revealed that the in-vitro germination rate of "clone C" red-fleshed pitaya decreased to <11% when pollen was stored for 3 months, but when the pollen intensity (pollen amount) was sufficient, the pollen remained able to promote fruit set by artificial pollination. Therefore, although pollen viability was significantly reduced under MH treatment, the function of the pistil was less affected by HT treatment.…”
Section: Discussionsupporting
confidence: 82%
“…For H. undatus, the highest average obtained was (99.87%), adjusted for 619 mg L −1 boric acid, which represents an increase of more than 100% in relation to the absence of this substance (Figure 5b). Metz et al (2000) worked with these two pitahaya species and found similar results for H. polyrhizus with an average germination of 82.8%, however, their results were divergent to the present study for the H. undatus species, which reached an average of 79.2%. Boric acid had the same effect for pollen grains germination of pear (Nogueira et al, 2016).…”
Section: Germination Ratecontrasting
confidence: 71%
“…• Phase III shows the pollen with a mealy characteristic, very manageable, easily detached from the anthers and it is precisely when the pollen samples observed the highest percentage of viable pollen. Metz et al [22] pointed out that for H. undatus and H. Polyrhizus pollen is more humid during the night, reducing in the morning. These data coincide with phases I and II, of the first part of the night, as well as with phase III, which occurs at dawn, which shed floury pollen due to the fact that it is more dehydrated.…”
Section: Resultsmentioning
confidence: 99%